Design a Website-Based Building Materials Inventory Information System At Tb.Gilang Putra - Tryana, Anjas; Damayanti, Santi (International Journal of Global Operations Research, 2023)
TB. Gilang Putra is a business engaged in the sale of building materials. In the processing of building material supplies, Tb.Gilang Putra uses manual processing. Then Tb.Gilang Putra needs an optimal program to improve its performance. Design a building material inventory information system is a system that will be built to reduce problems contained in the building material inventory information system. The loss and destruction of some data that prevents the data from being inputted. The method used in this building material inventory information system is object orientation (OOAD) and uses the Rational Unified Processes (RUP) model and is supported by Unified Modeling Language (UML) for software engineering processes with good structure. The author draws the conclusion that the system in this design can be useful and alleviate the process of supplying building materials and is able to solve problems that occur so that the system that is run can be used anytime and anywhere.Â